Superficial, shallow and reactive: How a small state news media covers politics - Ólafsson Jón Gunnar (Nordicom Review, 2021)
This article illustrates how the crisis of the news media is impacting political coverage in Iceland. Perceptions of routine political coverage in the Icelandic media have not been studied before, and this article fills this research gap and situates the Icelandic case within the wider news media crisis literature. My exploration is guided by two research questions. The first focuses on how journalists and politicians in Iceland perceive political coverage in the Icelandic media and how the coverage is seen to affect their working practices. The second question concerns how the public in Iceland perceives political news content. Findings show that, according to journalists and politicians, the mix of mainly commercial funding models and the smallness of the media market results in even more superficial and problematic coverage than in larger states. Survey answers illustrate that the public mostly agrees with interviewee perceptions concerning how the Icelandic media covers politics.